Spreadsheet-Based Car Engine Temperature And Compression Pressure Gauge - Wijaya Al Hadad Sudjono Putra; Jamaaluddin Jamaaluddin; Izza Anshory; Akhmad Ahfas (Journal of Computer Networks, Architecture and High Performance Computing, 2024)
Measuring the engine's temperature and compression pressure in cars is a crucial part of engine maintenance and performance evaluation. The objective of this study is to develop an accurate and efficient spreadsheet-based measurement system for determining engine temperature and compression pressure in automobiles. For this investigation, data from car engines was collected using engine temperature thermometers and compression pressure gauges. The collected data is then fed into a spreadsheet designed specifically to assess and automatically calculate engine temperature and compression pressure. The results show how reliable and accurate the measurements made using this spreadsheet-based measurement technique are. This approach's main benefits are also its flexibility and ease of use, since users can rapidly adapt the spreadsheet to the particular needs of the engine being tested. With this technology in place, car owners or professionals who do engine maintenance can quickly detect potential engine problems, such as valve leakage or unexpected temperature increases. Therefore, to increase fuel efficiency and extend engine life, spreadsheets can be utilized as a tool for measuring engine performance. The goal of this project is to facilitate the work of auto repair shop owners by utilizing the Esp8266 microcontroller for the DS18b20 sensor and compression sensor. Even so, there are several difficulties, like a sluggish internet connection that delays uploading data to the LCD and spreadsheets that are less useful because of a bad internet connection.